Analisis Strategi Mahasiswa PJKR UPGRIS Dalam Menjaga Kebugaran Jasmani Selama Masa Pandemi Covid-19 - Achmad Tegar Perdana (Journal of Physical Activity and Sports (JPAS), 2022)
The background of this research is based on being a student of the physical education, health, and recreation study program, it is very important to take an active role in breaking the chain of the spread of Covid-19 by making a strategy to maintain physical fitness to increase immunity resistance. This research is descriptive quantitative and the research design is a survey method by collecting information or data using a questionnaire. The data analysis technique in this study used t-test statistics. The instrument uses a closed direct questionnaire using a choice type questionnaire, namely: strongly disagree (1), disagree (2), neutral (3), agree (4), and strongly agree (5). The population in this study were active students of PJKR Upgris. The sampling technique is random sampling. Based on the test using SPSS 20, it shows that the regression coefficient value is 0.626, meaning that for every 1% addition to the physical fitness analysis (x), physical fitness during the pandemic (Y) will increase by 0.626. Thus, it can be said that strategy analysis (X) has a positive effect on physical fitness during the pandemic (Y). In addition, the results of the study also showed a sig value of 0.000 <0.05 and an at-count value of 8.659 > 0.227 so the hypothesis was accepted. From the results of testing these data, it can be concluded that the analysis of strategies in the exercise carried out by PJKR UPGRIS students has a positive and significant influence on improving physical fitness during the covid-19 pandemic. Based on the results of research conducted on PJKR Upgris students, it can be concluded that: There is an influence between the analysis of PJKR students' strategies in maintaining physical fitness during the Covid-19 pandemic. In this case, it can be interpreted that the influence of the analysis of the exercise strategy of PJKR Upgris students in helping to maintain physical fitness levels during the COVID-19 pandemic is significant.